ANALISIS RASIO KESEHATAN KEUANGAN PERBANKAN TERHADAP KINERJA KEUANGAN (Studi pada Perbankan yang Terdaftar di BEI Tahun 2020-2022) - Ridho, Ahmad Aulia; Kusumadewi, Rr. Karlina Aprilia (Diponegoro Journal of Accounting, 2024)
This study aims to examine the influence of the financial soundness ratios of banks, namely CAR, NPL, NIM, BOPO, and LDR, on bank financial performance as measured using the Return on Assets (ROA) value. The population in this study is banks listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. The number of samples used was 41 banks using the purposive sampling method. The analysis method used in this study is multiple regression test. The reason for this research is due to the decline in bank financial performance in Indonesia during the Covid-19 pandemic. So researchers are interested in identifying this by evaluating the level of financial health of banks.The results of this study show that NIM has a significant and positive effect on financial performance. CAR and BOPO have a significant and negative effect on financial performance. Meanwhile, NPLs and LDRs do not have a significant influence on financial performance. NPLs have no effect on the financial performance of banks in Indonesia because the value of NPLs is monitored by the Financial Services Authority (OJK). Meanwhile, LDR has no effect on financial performance because banks do not only depend on interest income from loans but have other sources of income so that the bank's financial performance can remain good even if the LDR is not optimal.